Building a Patient Navigation Program to Improve the Student and Patient Experience at a Student-Run Free Clinic - Arellano Zameza, Priscila; Robusto, Brian; Rong, Anita; Dunbar, Corrinne; Valente, Jessica (Journal of Student-Run Clinics, 2024)
Introduction: Patient navigation programs improve patients’ access to care. The existing literature on patient navigation programs affiliated with Student-run Free Clinics (SRFCs) is limited. The Patient Navigation Program (PNP) was developed to give health professions students early experience in patient-centered care while helping patients overcome barriers to care. First-year student volunteers at our SRFC, the Delivering Equal Access to Care (DEAC) clinic, have limited opportunities to participate in direct patient care. A subset of our patient population faces additional challenges accessing health-related services, resulting in a need for coordinated care. This descriptive report describes a sustainable patient navigation program designed to improve the student and patient experience at an SRFC. Methods: One medical director and three third-year medical students supervised all participants. First-year students from the Doctor of Medicine (MD) and Physician Associate (PA) programs applied for Patient Navigator (PN) positions, and upper-level students from the MD and PA programs applied for Navigation Manager (NM) positions. Two mandatory student trainings were provided, one led by the program’s medical director and the other by an associate professor in Psychiatry and Behavioral Medicine. Patients were referred from the primary care service. A voluntary, program satisfaction survey was emailed to PNs at the end of the year. Results: Seven of the eight PNs completed their 12-month commitment and one PN transitioned into another DEAC clinic leadership role before the end of the year. Seven PNs completed the survey, and all indicated wanting to stay involved with the program in some capacity. Four of seven (57%) respondents were interested in continuing with their current patient due to perceived ongoing needs. Perceived impact of PNP on patients’ health includes obtaining additional health services, reliable transportation, and someone to discuss health concerns. Discussion: Over half of PNs joined DEAC clinic leadership at the end of their 12-month commitment, pointing to the potential of patient navigator programs to develop committed leaders at SRFCs. Building a sustainable program like PNP at another SRFC is feasible and has potential for meaningful student and patient impact.